Wombat stew - Vaughan, Marcia K.; Lofts, Pamela (Morristown, N.J. : Silver Burdett Co., 1986)
A dingo intent on making wombat stew receives cooking suggestions from the other animals, unaware that they are protecting their fellow creature.
Elem. School Library Collection
School Library Journal
2.5
K-3
Keywords: Animals -- Fiction; Australia -- Fiction; Animals -- Fiction; Australia -- Fiction